Conversations With Long-Time Adult Educators - Deana Hensley; Patricia A. Maher; Denise Passmore (Adult Education Research Conference, 2001)
The purpose of this study was to collect and analyze information from long-time adult educators, to learn from their experiences, and to ensure the wisdom they have gained throughout their time spent in the field is not lost.